A morphological study of the ovipositor of the genus Capillogryllus Xie, Zheng & Liang, 2003 with a new species of the genus from China (Orthoptera: Gryllidae; Gryllinae) - Wu, Qian; Zhang, Tao; Ma, Li-Bin (Zootaxa, 2023)
The genus Capillogryllus includes three species, Capillogryllus dolabripalpis Xie & Zheng, 2003, Capillogryllus exilipalpis Xie & Zheng, 2003, Capillogryllus spinae Wu & Ma, 2023. Recently, we found a new species of this genus in Yadong County, Xizang Autonomous Region, and described it here. In addition, we found that the ovipositor varies greatly within this taxon, so we compare and characterize their ovipositor and discuss the feasibility of using the ovipositor alone to identify them. We also provide two keys based on the genitalia of males and females.